The Students’ Perspectives About the Effectiveness Argumentative Speaking Tasks Given on English Class - Tunzia Fadillah Dinda Maghfiroh; Mauly Halwat Hikmat (Universitas Majalengka, 2023)
Argumentative speaking skill is a communication process that aims to convince others to accept our opinions based on facts and strong evidence. The purpose of this study was to find out the students' perspectives about the effectiveness of argumentative speaking tasks given. This study used a qualitative method. The participants in this study were third semester students in English education of Universitas Muhammadiyah Surakarta. There were twenty participants in this study in class G. Data were collected using interviews using notes to record the results of the interviews and documentation in the form of student data instruments and taking pictures during the interviews. The result showed the students perceived that argumentative speaking tasks given was effective for students to form critical thinking and increased their speaking skills.